DISEASE ASSESSMENT KEY FOR POWDERY MILDEW OF MANGO - MAMTA; K. P. SINGH (The Bioscan, 2015)
In the present investigation, experiment was conducted to develop an assessment key for evaluating the powdery mildew incidence and per cent disease index on each twenty different mango cultivars. The study was conducted in randomized block design with three replications during cropping season 2013 and 2014. The incidence of disease was more in the commercially successful varieties like Dashehari (31.26%), Amrapali (31.42%) and was minimum in local variety Gaurjit (23.57%) in both the years. The maximum PDI was found in cultivars Amrapali (1.42%) and Rasgulla (1.41%), while minimum PDI was observed in cultivar Chausa (1.14%), Gorakhpurlangra (1.15%), Ramkela (1.15%) and (Gaurjit 1.15%) in both the years. The study indicated that during both the years of study the commercially grown cultivars like Amrapali and Dashehari were found to be more susceptible, and the local cultivar Gaurjit was least susceptible indicating the role of local cultivars in incorporating powdery mildew resistance in future mango breeding programme.